Callus induction from leaf explant of ficus deltoidea varkunstleri - Sa'adan, Hafizuddin; Zainuddin, Zarina (Zibeline International Publishers, 2020)
Ficus deltoidea or commonly known as ‘mas cotek’ is a herbal plant indigenous to Southeast Asia including Malaysia and Indonesia. This plant is popular for its medicinal values such as improve blood circulation, regain energy and enhance fertility naturally for both men and women. The main objective of this study is to develop in vitro clonal propagation method for rapid production of F. deltoidea using different concentrations of benzyl aminopurine (BAP) through shoot induction and multiplication, rooting and subsequent establishment in soil following acclimatization. Surface sterilization of the leaf explants was done using mercury chloride and ethanol as the disinfectants. Pre-treatment of the explants with carbendazim successfully reduced the occurrence of fungal contamination. At the end of the experiment, no shoot and root induction were observed but calli were successfully induced on MS medium containing 1.0, 1.5, 2.0, 2.5 and 3.0 mg/l BAP, with calli induced from 3.0 mg/l BAP were bigger and healthier. In short, the higher the concentration of BAP used, the higher tendency for the explant to induce callus.